29 seconds - Logan, T. M. (St. Martin's Press, 2019)
Sarah is a young professor struggling to prove herself in a workplace controlled by the charming and manipulative Alan Hawthorne, a renowned scholar and television host. The beloved professor rakes in million-dollar grants for the university where Sarah works - so his inappropriate treatment of female colleagues behind closed doors has gone unchallenged for years. And Sarah is his newest target. When Hawthorne's advances turn threatening, she's left with nowhere to turn. Until the night she witnesses an attempted kidnapping of a young child on her drive home, and impulsively jumps in to intervene. The child's father turns out to be a successful businessman with dangerous connections - and her act of bravery has put this powerful man in her debt. He lives by his own brutal code, and all debts must be repaid. In the only way he knows how. The man gives Sarah a burner phone and an unbelievable offer. A once-in-a-lifetime deal that can make all her problems disappear. No consequences. No traces. No chance of being found out. All it takes is a 29-second phone call. Because everyone has a name to give. Don't they?